The effect of work-family conflict towards job satisfaction and emotional well-being: problem-focused coping as mediator - Norizan Baba Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Inability to cope with conflicting demands of work and family has become an important topic among the employees in organisation. However, studies on inability to cope with conflicting demands on work, family and distance learning among the distance learners in Malaysia have received little attention. In this article, a sample of distance learners (N=173) were utilized to examine the relationship between work-family conflict towards problem-focused coping, job satisfaction and emotional well-being, and to examine the mediating effect of problem-focused coping between work-life conflict towards job satisfaction and emotional well-being. The research model was tested upon Coping Theory and Self-Determination Theory. Results of Partial Least Square (PLS) demonstrated that work-family conflict has a positive influence only on problem-focused coping, and subsequently problem-focused coping was found to mediate the relationship between work-life conflicts towards job satisfaction and emotional well-being. Based on the findings, this research suggests the employers to enhance work-life balance policies and programmes especially for employed distance learners, and the management of distance education to improve student retention and completion rates by providing supports to the distance learners.